PERANAN KEGIATAN RELAWAN PAJAK DALAM MENDUKUNG PELAKSANAAN STIMULUS FISKAL PEMERINTAH TAHUN 2020 - Dwikora Harjo; Aprilia Alfani; Wahidin Septa Zahran; Iwan Irwansyah (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
This research is a combination of field and literature research, namely analyzing the perceptions of individual taxpayers in reporting the Annual Tax Return on the assistance of tax volunteers. In analyzing using the theory of usefulness and convenience based on literature in the form of books, journals by combining the data obtained from the answers of individual taxpayers. The research objective was to determine the perception of individual taxpayers on the satisfaction of assistance carried out by tax volunteers at the tax volunteer placement location. There are 5 (five) locations for the placement of Tax Volunteers, namely West Bekasi Tax Office, Pondok Gede Tax Office, North Bekasi Tax Office, South Bekasi Tax Office, and STIAMI Institute Tax Center. This research use desciptive qualitative approach. The sampling technique used in this study was purposive sampling with interview techniques in collecting research data. The population in this study are taxpayers who carry out the obligation to report their annual tax return through e-Filing. Meanwhile, the sample in this study were taxpayers whose annual SPT reporting activities were accompanied by tax volunteers in these 5 (five) placements. The results of this study indicate that taxpayer assistance activities by tax volunteers in helping to fill individual annual tax returns are very effective. This can be seen from the satisfaction of taxpayers after receiving assistance by tax volunteers. Taxpayers are satisfied with the assistance of tax volunteers because the annual SPT reporting process is easier, faster and tax volunteers are able to guide taxpayers in filling out their SPT